Clinical performance of short implants vs. standard implants in edentulous patients. An umbrella review - Arbildo-Vega, Heber Isac; Cruzado-Oliva, Fredy Hugo; Infantes-Ruíz, Edward Demer; Luján-Valencia, Sara Antonieta; Meza-Málaga, Joan Manuel; Marroquín-Soto, Consuelo; Coronel-Zubiate, Franz Tito (Frontiers in Oral Health, 2025)
AimTo assess the clinical performance of short implants compared to standard-length implants in edentulous patients through an umbrella review.Material and methodsA comprehensive search was conducted in databases such as PubMed, Cochrane Library, Scopus, SciELO, Google Scholar, ProQuest Dissertations and Theses, and OpenGrey, covering literature up to June 2025. Included studies were systematic reviews, with or without meta-analysis, that compared short implants with standard-length implants, with or without bone augmentation, reporting on implant survival, marginal bone loss, and biological or prosthetic complications. Reviews of a narrative nature, rapid reviews, clinical trials, observational or experimental studies, case reports, editorials, letters, protocols, and posters were excluded. The methodological quality of the reviews was assessed using the AMSTAR-2 tool.ResultsFrom an initial retrieval of 790 records, 60 systematic reviews met the inclusion criteria. The data showed no significant differences in survival rates, implant failure, or prosthetic complications between short and standard implants. However, short implants showed less marginal bone loss and fewer biological complications.ConclusionBased on high-confidence systematic reviews, short implants provide comparable clinical outcomes to standard-length implants and are a viable, less invasive alternative for patients with reduced vertical bone height.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42020218497, PROSPERO CRD42020218497.